Perspektif Gender dalam Novel Kubah di Atas Pasir Karya Zhaenal Fanani: Tinjauan Sastra Feminis dan Implementasinya dalam Pembelajaran Sastra di SMA - Ratnasari, Dinna, Prof. Dr. Ali Imron Al-Ma'ruf, M.Hum (2017)
This research aims to (1) describe the socio-historical background as a novelist Zhaenal Fanani the Dome in Upper Sand. (2) describe the elements that build the Dome of the short stories in the Upper Sand Zhaenal fanani work. (3) describe the gender perspective in the novel The dome in Upper Sand Zhaenal Fanani work, and (4) describe the implementation of a gender perspective in the novel The dome in Upper Sand from the research results. This research is a descriptive qualitative research. The object of this study are the words contained in the Dome in the Upper Sand novel Zhaenal Fanani work. Data from this research is a sentence in the novel and the Dome in Upper Sand works Zhaenal Fanani and the sentence that contains the gender perspective of gender injustice and gender equality.Sources of data in this research sentence in the novel The dome in Upper Sand Fanani Zhaenal work. Data collected by the trailer which is purposive sampling. The data analysis is done by reading heruistik and hermeneutics. The results were obtained based on the formulation of the problem which include (1) The socio-historical background Zhaenal Fanani born on 7 March 1964 at Dampir, Malang, East Java. (2) Elements that build novel the Dome in Upper Sand Fanani Zhaenal work includes themes, characters, lattar and groove. The theme in this novel there is a woman behind the simplicity of exceptional strength. The main character is Fatikha he has a good attitude and aat worship. Lattar occurred in the village Ngurawan, schools, foundations Ar-Rahman mosque in Ngurawan, Police Blumbang. Flow in this novel is the flow of the mixture. (3) A gender perspective in the novel The dome in Upper Sand works Zhaenal Fanani of gender equality and gender injustice. Gender equality related negative labeling in women, as a secondary figure in the modern era. Gender inequity regarding how a woman is still considered secondary position is always under male. (4) Implementation of learning in high school might refer to how to understand the novel is used as a teaching of understanding characterizations, story content and background of the novel.